Islamic Senior High School Students’ Language Learning Strategies and their English Achievement - ISTI QOMARIAH (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2018)
This study investigated the correlation between language learning strategies and English achievement, and explored the influence of language learning strategies on English achievement of eleventh grade students’ of MAN 3 Palembang. A total of 141 eleventh grade students participated in this study. The questionnaire and test were used to collect the data. For this purpose, the language learning strategies (SILL) questionnaire developed by Oxford (1989) measured language learning strategies and TOEFL junior (2015) was used to know students’ English achievement. There were three levels from high to low based on the results of SILL questionnaire and five categories English achievement test. Descriptive stastistic, pearson product moment correlation and regression anlaysis were employed to analyze the data. Based on the data analysis, it was found that r (.665) > rtable (.165) with significant level which was lower than 0.05. Thus, it indicated that there was significant correlation between language learning strategies and English achievement. It was implied that good language learners caused good in English achievement.